2018
DOI: 10.3390/jsan7030034
|View full text |Cite
|
Sign up to set email alerts
|

Enif-Lang: A Specialized Language for Programming Network Functions on Commodity Hardware

Abstract: The maturity level reached by today’s commodity platforms makes even low-cost PCs viable alternatives to dedicated hardware to implement real network functions without sacrificing performance. Indeed, the availability of multi-core processing packages and multi-queue network interfaces that can be managed by accelerated I/O frameworks, provides off-the-shelf servers with the necessary power capability for running a broad variety of network applications with near hardware-class performance. At the same time, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The authors of [16] have identified the principles for the edifice of elevated functioning of software router organisms on commodity hardware. The level of commodity platforms has reached at a place where the production of low-cost hardware with viable alternatives is very much possible with their implementation to the real-time network functions without forfeiting the performance [17]. Further development of these systems needs secure environment where old hardware can be used as effective infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [16] have identified the principles for the edifice of elevated functioning of software router organisms on commodity hardware. The level of commodity platforms has reached at a place where the production of low-cost hardware with viable alternatives is very much possible with their implementation to the real-time network functions without forfeiting the performance [17]. Further development of these systems needs secure environment where old hardware can be used as effective infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, programs can run directly on the switch data path with maximum performance. For general purpose platforms, the PFQ I/O framework [6] provides a programming language especially devoted for packet processing [14], [15] in a streaming fashion based on a functional algebra [16].…”
Section: Related Workmentioning
confidence: 99%
“…While the above approaches target programmable hardware nodes, other programming abstractions for software solutions have been made available in the meantime. Enif-lang [ 14 ] extends the works in [ 15 , 16 ], providing a tool for programming generic network functions on the Linux Operating System (OS). Program safety and correctness are enforced thanks to its strongly typed nature, inherited from the underlying used Haskell functional language.…”
Section: Introductionmentioning
confidence: 99%